Identifikasi Bakteri pada Ikan Asap yang Dipasarkan di Pasar Pharaa Kabupaten Jayapura - Samuel Jeujanan (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The current need of society for the importance of good quality food has required any food producers, particularly smoked fish to make the food available on the market. The quality and safety requirements of smoked fish have been regulated in the Indonesian National Standard. The possibility of bacterial contamination and other factors causing the quality of smoked fish marketed at Pharaa market, Jayapura Regency is very possible, so this research is necessary. The purpose of the study was to identify the presence of bacteria in smoked fish marketed in the Pharaa market, Jayapura Regency. The method applied is to buy smoked skipjack tuna (Katsuwonus pelamis) which is sold at Pharaa Market, then brought to the laboratory for identification. In addition, the testing for Salmonella sp. and Staphylococcus aureus refers to SNI 2897:2008. The research was conducted for three months, from August to October 2021. The finding reveals that the entire sample of smoked fish marketed at Pharaa market, Jayapura Regency, is still fit for consumption. The results showed that no indication of bacteria Salmonella sp and Staphylococcus aureus on smoked fish. In the meantime, in accordance with the Indonesian National Standard (SNI) 2725:2013, the quality and safety requirements of smoked fish with hot smoking are negative for Salmonella sp. and Staphylococcus aureus is max. 1.0 x 103.